A prática de lembrar e a aprendizagem ortográfica em crianças de escola pública - Francine Veiga da Silva (2022)
Several studies have shown that the act of trying to remember recently memorized information increases the chance of that information being later remembered. For this reason, this “retrieval practice” has been proposed as a technique that can benefit teaching and learning processes. However, almost all the studies that investigated this phenomenon were conducted with students from North American universities and schools. Therefore, we aim to verify whether retrieval practice can be an effective strategy for teaching orthography to children studying in Brazilian public schools. To achieve this goal, we conducted two experiments with 5th grade children from a public school. In the first, children were exposed to 30 words with moderate difficulty orthography for this age group. The words were presented individually on a digital whiteboard and after this exposition was finished, there was a brief interval, after which half of the words were re-presented on the digital whiteboard while they were simultaneously read by the experimenter. The children's task was to copy the words as correctly as possible on a sheet intended for this purpose (copy condition). The other half of the words were just dictated aloud by the experimenter, and children had to write them as correctly as possible based on what they remembered from the first exposure (retrieval practice condition). After an interval of 4 days, the same words were spoken aloud by the experimenter, and children wrote them down as correctly as they could, a task that was followed by a multiple-choice test. Experiment 2 was identical to experiment 1, with the exception that a total of 20 words were used, and that each response was followed by corrective feedback. While in experiment 1 children showed similar later performances for the copy and retrieval practice conditions, in experiment 2, orthographical performance for retrieved words was significantly greater than for copy condition. Since only in experiment 2 the practice of remembering was followed by corrective feedback, our findings suggest that this practice can be an excellent strategy to teach orthography for children, although only when it is followed by corrective feedback.